Size Only Matters If You Have Vision: An Exploration of an Urban e-Learning Cluster - Michael K Barbour; Jason P Siko (Flexible Learning Association of New Zealand, 2020)
Historically, primary and secondary distance education in New Zealand was focused on providing opportunities for rural students. With the advent of Tomorrow's Schools, the need for rural schools to compete with urban schools in terms of their curricular offerings were one of the reasons for the creation of e-learning clusters that would eventually become the Virtual Learning Network (VLN). After 25 years of practice, there is a growing body of research into these rural e-learning clusters. However, in 2011 the HarbourNet cluster bucked that trend, and became the first active urban-based VLN program. This study begins to address this research gap by exploring the challenges HarbourNet was able to overcome in order to become a successful member of the VLN.